REGARDING THE PROVISION OF NATIONAL MINORITY RIGHTS IN THE CENTRAL ASIAN STATES - Xomitov R. X (TARIXIY TADQIQOTLAR, 2026)
In this article, aspects such as participation in international law norms in multiethnic societies in Central Asian countries, provision of rights and freedoms of national minorities in them are studied. In particular, human rights in the countries of the region, mainly the contents of the state policy regarding the national minority are described